Feasibility of absolute quantification for 31P MRS at 7 T. Issue 1 (20th March 2019) - Purvis, Lucian A. B.; Valkovič, Ladislav; Robson, Matthew D.; Rodgers, Christopher T.
Abstract : Purpose: Phosphorus spectroscopy can differentiate among liver disease stages and types. To quantify absolute concentrations of phosphorus metabolites, sensitivity calibration and transmit field ( B 1 + ) correction are required. The trend toward ultrahigh fields (7 T) and the use of multichannel RF coils makes this ever more challenging. We investigated the constraints on reference phantoms, and implemented techniques for the absolute quantification of human liver phosphorus spectra acquired using a 10‐cm loop and a 16‐channel array at 7 T. Methods: The effect of phantom conductivity was assessed at 25.8 MHz (1.5 T), 49.9 MHz (3 T), and 120.3 MHz (7 T) by electromagnetic modeling. Radiofrequency field maps ( B 1 ± ) were measured in phosphate phantoms (18 mM and 40 mM) at 7 T. These maps were used to assess the correction of 4 phantom 3D‐CSI data sets using 3 techniques: phantom replacement, explicit normalization, and simplified normalization. In vivo liver spectra acquired with a 10‐cm loop were corrected with all 3 methods. Simplified normalization was applied to in vivo 16‐channel array data sets. Results: Simulations show that quantification errors of less than 3% are achievable using a uniform electrolyte phantom with a conductivity of 0.23‐0.86 S.m −1 at 1.5 T, 0.39‐0.58 S.m −1 at 3 T, and 0.34‐0.42 S.m −1 (16‐19 mM KH2 PO4(aq) ) at 7 T. The mean γ‐ATP concentration quantified in vivo at 7 T was 1.39 ± 0.30 mmol.L −1 to 1.71 ± 0.35 mmol.L −1 wet tissue for the 10‐cm loop and 1.88 ± 0.25 mmol.L −1 wet tissue for the array. Conclusion: It is essential to select a calibration phantom with appropriate conductivity for quantitative phosphorus spectroscopy at 7 T. Using an 18‐mM phosphate phantom and simplified normalization, human liver phosphate metabolite concentrations were successfully quantified at 7 T.